TANGGUNG JAWAB JAKSA SEBAGAI LIKUIDATOR DALAM PROSES PEMBUBARAN PERSEROAN TERBATAS (STUDI KASUS PENETAPAN NOMOR 659/PDT.P/2020/ PN.JKT.BRT) - Martin Fredrik; Megawati Barthos (Constitutum: Jurnal Ilmiah Hukum, 2024)
The dissolution of a Limited Liability Company (PT) can be carried out by a District Court order upon the request of the Prosecutor's Office, based on the grounds that the PT has committed acts violating statutory regulations. In this case, the Prosecutor, acting as the liquidator, plays an essential role in the dissolution, liquidation, and settlement processes of the PT. Based on this, this study will analyze the case of PT. Gemilang Sukses Garmindo in District Court Order Number 659/Pdt.P/2020/PN.Jkt.Brt. The dissolution process of PT. GSG, starting from the initial review by the State Attorney at the West Jakarta Prosecutor's Office to the District Court Order Number 659/Pdt.P/2020/PN.Jkt.Brt., was in accordance with the Attorney General's Regulation Number Per-025/A/JA/11/2015 and represents the best step determined by the Judge for effectiveness and efficiency. The Prosecutor's reason for filing the dissolution request of PT. GSG was that PT. GSG was proven legally and convincingly guilty of committing tax crimes as stipulated in Article 39A letter a of Law Number 16 of 2009 concerning General Provisions and Tax Procedures. The Prosecutor, as the liquidator, is responsible for the liquidation of PT. GSG as regulated in Article 147 paragraph (1), Article 148 paragraph (2), Article 149 paragraph (1), and Article 152 of Law Number 40 of 2007 concerning Limited Liability Companies.